Marginal Adaptation of Cerec 3 CAD/CAM Composite Crowns Using Two Different Finish Line Preparation Designs - Jaber Hussain Akbar, DDS, MS;1 Cynthia S. Petrie, DDS, MS;2 (Journal of Prosthodontics, 2006)
The purpose of this study was to compare marginal discrepancies of Cerec 3 CAD/CAM composite crowns, fabricated on human prepared teeth with two different finish line designs, chamfer and shoulder.